Lived religion: Faith and practice in everyday life - Mcguire, Meredith B. (New York Oxford University Press, 2008)
What are we to make of the Latina schoolteacher who considers herself a good Catholic, rarely attends Mass, but meditates daily at her home altar (where she mixes images of the Virgin of Guadalupe with those of Frida Kahlo, and traditional votive candles with healing crystals), yet feels particularly spiritual while preparing food for religious celebrations in her neighborhood? Diverse religious practices such as these have long baffled scholars of contemporary religion, whose research started with the assumption that Individuals commit, or refuse to commit, to an entire institutionally-defined package of beliefs and practices.